PERSPEKTIF MASLAHAH MURSALAH TERHADAP IMPLEMENTASI PP NOMOR 48 TAHUN 2014 TENTANG BIAYA PERNIKAHAN DI KANTOR URUSAN AGAMA (KUA) KECAMATAN GONDANG - M.FARHAN ADZKIYA; MUHAMMAD (JOURNAL SAINS STUDENT RESEARCH, 2024)
This thesis is the result of the author's research and thoughts entitled "Implementation of Government Regulation Number 48 of 2014 concerning Wedding Costs in the Religious Affairs (KUA) office of Gondang District, Maslahah Murlah Perspective." This research aims to answer the questions stated in the problem formulation. The type of research the author uses is qualitative, applying a qualitative descriptive approach. The data collection methods used are interviews, observation, documentation. The results of this research show that 1) According to Government Regulation Number 48 of 2014 concerning Amendments to Government Regulation Number 47 of 2004 concerning tariffs for types of Non-Tax State Revenue Applicable to the Department of Religion, marriage or reconciliation at the Office of Religious Affairs on working days and hours is subject to tariff is 0 (zero) rupiah, 2) the public also gets certainty regarding marriage tariffs so that no one suffers a loss because it is open and transparent. 3) the implementation of this regulation has succeeded in achieving the goal of facilitating the implementation of marriages efficiently and fairly, in accordance with human values in Islamic law